Presentation Forms of the Usung Bausung Dance by the Nuansa Seni Studio in Banjarmasin City - Wardani, Ihda; Yanuar Nugraheni, Edlin; Permata Kumala Sari, Putri Yunita (Jurnal Seni Tari, 2024)
The Usung Bausung dance is a new traditional dance creation with a folk theme that depicts the life of the Banjar people when using the Bausung tradition in Banjar traditional weddings. The purpose of the study was to describe the form of presentation and factors that influence the form of presentation of the Usung Bausung dance. The study used the descriptive qualitative method. Data collection techniques were interviews, observation, and documentation. The data analysis stage used data reduction, data presentation, and conclusion. The results obtained from the form of presentation in the Usung Bausung dance include presentations on movements resulting from developing dance movements in Banjar and several meaningful movements such as Ba`akad and Bausung movements. The music used is in the form of Banjar gamelan music. The make-up used by female dancers is catik in Matahagi. The clothes used are a combination of Banjar dancer clothes with a folk theme and Banjar traditional wedding clothes. In addition, accessories used are yellow cloth, gepang horses, cupu, and scarves. The floor pattern is arranged creatively with vertical, circular, horizontal, and diagonal shapes. The lighting arrangement is more dominant in bright yellow mixed with white. The performance venue is in the form of a proscenium. Factors that influence the form of dance presentation are internal factors originating from the arrangers in influencing the form of presentation in the process of its creation. External factors are the habits of the Banjar community in carrying out the Bausung tradition at Banjar traditional weddings.